Comportamento morfo-fisiológico de Commelina benghalensis em resposta a herbicidas aplicados em pós-emergência - Krolikowski, Valquiria [UNESP] (2015)
The genus Commelina, the spiderwort are considered weeds in all cultures in the world. Besides harming crops, the spiderwort also infest farms and vacant lots across the country. Difficulties in control of Commelina benghalensis with existing herbicides are observed in the field, so this study aimed to assess the control of C. benghalensis, after application of herbicides in five stages. The plants were grown in pots containing 2 L Bioplant substrate and soil being maintained throughout the experiment in a greenhouse of the Paulista State University Julio Mesquita Filho - Faculty of Engineering. The experimental design was completely randomized with four replications in factorial 8 x 5, so 7 herbicides in recommended commercial rates (atrazine, carfentrazone, flumioxazin, glyphosate, metanoarseniato ácido monossodico (MSMA),, nicosulfuron, paraquat and a control applied 5 in phenological stages adjusted the BBCH scale (two true leaves or leaf cartridge not distended - BBCH 11, three true leaves or leaf cartridge not distended - BBCH 12; First stem visible side - BBCH 21; Two visible side stems - BBCH 22 and early flowering, with twenty tillers - BBCH 51). It was observed that the growth stage of the plants affects the efficiency of chemical control. Plants in the early stages of development (BBCH 11 and 12) were more susceptible to herbicides, however occurring control in its entirety only with atrazine herbicides, carfentrazone, MSMA and paraquat. Despite suffering heavy injuries C. beghalensis have tolerance compared of another treatments